2004
DOI: 10.1002/ange.200460326
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mode Determination of Benzimidazole Inhibitors of the Hepatitis C Virus RNA Polymerase by a Structure and Dynamics Strategy

Abstract: Eine neuartige Strategie, die NMR‐Spektroskopie, medizinische Chemie und Molecular Modeling umfasst, diente zur Bestimmung der Bindungsweise von Liganden und der Rolle ihrer Substituenten dabei. Diese erste Lösungsstruktur eines an die Hepatitis‐C‐Virus(HCV)‐Polymerase gebundenen Inhibitors (siehe Bild) liefert wertvolle Informationen für das rationale Design potenzieller Wirkstoffe gegen HCV‐Infektionen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Many NNIs have already been reported. One example is benzimidazoles, which bind to the thumb domain of NS5B [ 3 , 7 - 10 ], while another is thiophene derivatives which are reversible allosteric inhibitors that also bind to the thumb domain [ 11 ], yet the binding sites in the thumb domain for the two inhibitors are different. X ray crystallographic studies have revealed that phenylalanine and dihydropyranone scaffold inhibitors bind to the same site in NS5B, although they have different chemical structures [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many NNIs have already been reported. One example is benzimidazoles, which bind to the thumb domain of NS5B [ 3 , 7 - 10 ], while another is thiophene derivatives which are reversible allosteric inhibitors that also bind to the thumb domain [ 11 ], yet the binding sites in the thumb domain for the two inhibitors are different. X ray crystallographic studies have revealed that phenylalanine and dihydropyranone scaffold inhibitors bind to the same site in NS5B, although they have different chemical structures [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme-bound conformation of a benzimidazole inhibitor, as determined by NMR experiments, suggests that indole-and benzimidazole-based inhibitors bind to the same allosteric binding site (LaPlante et al, 2004). This binding site was elucidated by Di Marco and colleagues (Di Marco et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…[24] These molecules inhibit NS5B by preventing formation of intramolecular contacts between the fingers and thumb domains and consequently preclude their coordinated movements during RNA synthesis. [25,26] We and others discovered that indole acetamides, such as 1, are potent inhibitors of the HCV NS5B polymerase, endowed with cell-based potency ( Figure 1). [27] Reports from our laboratories have documented the evolution of 1 to more potent indole acetamides such as 2, [21,28] as well as to tet-racyclic indoles [29] as exemplified by 3.…”
Section: Introductionmentioning
confidence: 99%
“…After stirring for 2 h at RT and work-up as described for compound 18 a, the residue was dissolved in THF (1 mL) and treated with aq HCl (1.0 mL, 1 n). [ (26): A solution of 21 c (50 mg, 0.104 mmol) in EtOAc (2.0 mL) was treated with 10 % Pd/C (5 mg) and stirred overnight. Additional Pd catalyst (5 mg) was added and the mixture was stirred for a further 24 h. The catalyst was filtered off and the filtrate concentrated in vacuo to give 25 (40 mg, 88 % yield) that was used without purification.…”
mentioning
confidence: 99%